Analysis of Electrical Inspection and Testing Implementation in Supporting Occupational Safety and Health at PT Cipta Pratama Inspeksi Indonesia - Jumaedi, Jumaedi; Kartika, Iin Ira; Triyuliana, Chaerani; Widhiantika, Wieke; Darmawan, Wendi; Fitriyastanti, Devi; Azhari, Yasin; Rismaya, Aulia Mei (Jurnal Kesehatan dan Kedokteran, 2025)
Electrical systems are essential infrastructures in industrial operations, but they also present significant occupational hazards such as electric shock, short circuits, equipment failure, and electrical fires. Inadequate electrical safety management may cause workplace accidents, operational disruption, and financial losses. Therefore, this study aims to analyze the implementation of electrical inspection and testing activities at PT Cipta Pratama Inspeksi Indonesia, particularly in administrative procedures, technical testing, reporting mechanisms, and documentation management within occupational safety practices. This study employed a descriptive qualitative approach. Data were collected through direct observation, documentation, and literature review, while data were analyzed using descriptive qualitative analysis involving data reduction, categorization, interpretation, and conclusion drawing. The findings show that electrical inspection and testing activities were implemented systematically through administrative verification, visual inspection, insulation resistance testing, grounding measurement, protective system verification, and structured reporting. These activities were conducted based on occupational electrical safety standards and supported by standardized operational procedures. The reporting and documentation systems also functioned as important mechanisms for accountability, regulatory compliance, and corrective action. This study implies that systematic electrical inspection should be integrated into Occupational Safety and Health Management Systems (OSHMS/SMK3) to strengthen workplace safety culture and industrial risk management. The originality of this study lies in its comprehensive analysis of electrical inspection implementation by integrating administrative preparation, technical testing, reporting, and documentation management within one analytical framework. Unlike previous studies that mainly focused on theoretical safety concepts or technical standards separately, this study provides empirical insight into the practical implementation of occupational electrical inspection systems in an Indonesian inspection service company.